Online Learning Class Setting of Recurrent Human Factor Training for Aircraft Maintenance Engineer License Holder - Widoro, Ego; Kurniawan, Andri; Arrafat, Bhima Shakti (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
This study discusses the class setting for online recurrent human factor training for AMEL holders. The online class setting for recurrent human factor training was developed to meet the needs for implementing training without requiring AMEL holders to return to class, while still meeting the training objectives. The study explores specific examples of learning methods, including a mix of lectures, discussions, and group work. It also considers the use of blended learning classes, particularly in the flipped classroom format, and the option of including a problem-based learning approach. Further research is needed to develop a recurrent human factors training class setting and examine its effectiveness.